2003
DOI: 10.1021/la026847l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of de Novo Designed Peptides Interacting with the Lipid-Membrane Interface on the Stability of the Cubic Phases of the Monoolein Membrane

Abstract: Elucidation of the mechanism of transitions between the cubic phase and the liquid-crystalline (LR) phase and between different cubic phases is essential for an understanding of the dynamics of biomembranes and the development of new crystallization techniques. Recently, we found that electrostatic interactions due to the surface charges of lipid membranes induce transitions between the cubic phase and LR phase and between different cubic phases (Aota-Nakano, Y.; Li, S. J.; Yamazaki, M. Biochim. Biophys. Acta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 40 publications
7
48
0
Order By: Relevance
“…Therefore, it is worthy noting that in our study the presence of bilayer-forming peptide in the MO/A 6 D mixture promotes the formation of H 2 instead of the planar L α (structure with zero curvature). Different findings were reported by Yamazaki and his coworkers [62] on the effect of the positively charged peptide WLFLLKKK, which was loaded with similar concentrations, onto the MO-based Pn3m phase. This peptide with a relatively large positively charged headgroup (KKK) induces the structural transformation from V 2 (Pn3m) via V 2 (Im3m symmetry) to L α .…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Therefore, it is worthy noting that in our study the presence of bilayer-forming peptide in the MO/A 6 D mixture promotes the formation of H 2 instead of the planar L α (structure with zero curvature). Different findings were reported by Yamazaki and his coworkers [62] on the effect of the positively charged peptide WLFLLKKK, which was loaded with similar concentrations, onto the MO-based Pn3m phase. This peptide with a relatively large positively charged headgroup (KKK) induces the structural transformation from V 2 (Pn3m) via V 2 (Im3m symmetry) to L α .…”
Section: Resultsmentioning
confidence: 59%
“…In a basic approach, the molecular shape can be described by the critical packing parameter (CPP) or the molecular wedge shape factor, which is defined as:where v s is the hydrophobic chain volume, a 0 is the headgroup area, and l is the hydrophobic chain length [73]. This packing parameter is controlled by various factors such as surfactant's molecular shape, temperature, hydration, the presence of hydrophilic or hydrophobic guest molecules, and electrostatic effects [16], [29][33], [35], [45][50], [61], [62].…”
Section: Resultsmentioning
confidence: 99%
“…15,16 As the peptide concentration increased and, thereby, the surface charge density of the MO membrane due to the bound peptide in the interface increased, the most stable phase of the MO membrane changed as follows: Q 224 w Q 229 w L R . 15,16 In biological cells, proteins and peptides may change stability of the cubic phases of biomembranes. Several peptides such as the so-called fusion peptides of membrane proteins in viruses have been reported to induce nonbilayer membranes such as the cubic phase and hexagonal (H II ) phase.…”
Section: Introductionmentioning
confidence: 99%
“…One family of cubic phases, which includes the Q 224 phase (space group Pn3m, Schwartz's D surface), Q 229 phase (Im3m, P surface) and Q 230 phase (Ia3d, G surface), has an infinite periodic minimal surface (IPMS) consisting of bicontinu-ous regions of water and hydrocarbon [17][18][19]. We have found that, as the concentration of peptide-1 increased, a phase transition from Q 224 to Q 229 occurred, and that, at higher peptide-1 concentrations, MO/peptide-1 membranes were in the L α phase [16]. Salts in solution inhibited these phase transitions, indicating that electrostatic interactions with adsorbed peptide-1 in the membrane interface induced these phase transitions.…”
Section: Analysis Of Shape Changes Induced In Guvs By the Interacmentioning
confidence: 95%
“…3). We have investigated the effect of peptide-1 on the stability of electrically neutral lipid membranes in the liquid-crystalline (L α ) phase [8] and in the cubic phase [16].…”
Section: Analysis Of Shape Changes Induced In Guvs By the Interacmentioning
confidence: 99%